CC Coupling of N‐Heterocycles at the fac‐Re(CO)3 Fragment: Synthesis of Pyridylimidazole and Bipyridine Ligands. Issue 19 (1st April 2014) - Viguri, Maialen Espinal; Pérez , Julio; Riera, Lucía
Abstract A new family of cationic rhenium tricarbonyl complexes with either two N‐alkylimidazole (N‐RIm) and one pyridine (Py) ligand, or two pyridine and one N‐RIm ligand, [Re(CO)3(N‐RIm)(3−x)(Py)x]+, has been prepared. The reaction of these complexes with a strong base, followed by an oxidant, selectively afforded 2, 2'‐pyridylimidazole complexes as the result of intramolecular dehydrogenative CC coupling reactions. For tris(pyridine) complexes [Re(CO)3(Py)3]+ the reaction pattern upon a deprotonation/oxidation sequence is maintained, which allows the generation of complexes with 2, 2'‐bipyridine ligands. In the particular combination of two different types of pyridine ligand in the cationic fac‐Re(CO)3 complexes only the cross‐coupling products with asymmetric 2, 2'‐bipyridine ligands were obtained; the homocoupling products were not observed.